THE EVALUATION OF Spirulina platensis DIETARY SUPPLEMENTATION ON THE GROWTH PERFORMANCE AND COLOR QUALITY OF POLAR BLUE CICHLID (Archocentrus nigrofasciatus × Amphilophus citrinellus) - Azril, Muh.; Wulan, Rahayu; Asri, Yuliana; Tartila, Shobrina Silmi Qori; mujtahidah, tholibah; Aji, Candra Purnomo; Setiani, Novia Ardhita; Wahyudi, Brillian Rossi; Widianto, Ikhwan Nursalman; Zusron, Muhammad (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2024)
This study aimed to evaluate S. platensis powder dietary supplementation on the growth performance and color quality of polar blue cichlids. This study used a completely randomized design experimental method with four different dietary supplementation doses of S. platensis powder, namely 10 g/kg diet (A), 20 g/kg diet (B), 30 g/kg diet (C), and 0 g/kg diet (K). These treatments were replicated four times. The polar blue cichlids as fish samples had 4.07 ± 0.12 cm and 2.15 ± 0.22 g. Diets (38% protein) were produced by coating the commercial feed with S. platensis powder in appropriate dosage. Feeding was performed until apparent satiation twice a day for 45 days. All parameters, including growth performance (feed intake, weight gain, length gain, specific growth rate, feed conversion ratio, survival rate) and color quality (total grid percentage and total chromatophores), were analyzed using an analysis of variance and the Duncan's multiple range test was applied to obtain the best treatment in growth performance and color quality. The dietary supplementation of S. platensis powder had no significant effect on the growth performance of polar blue cichlids. However, this treatment provides a higher total grid percentage of blue color and total chromatophores in the fish. The best treatment on color quality was found in a 30 g/kg diet dose of S. platensis powder. Therefore, 30 g/kg dose of S. platensis powder is effective to improve the color quality of polar blue cichlids, although providing no significant effect on the growth of the fish.